Identicifation of isotropic hardening parameters for stainless steel sheet by cyclic loading tool - Ng, Kok Hwang (2013)
This project presents the new developed experiment tools for bending and unbending test to identify the parameters hardening of isotropic equation. Stainless steel is used as specimen due to it very widely used in many industries. This experiment helps to improve the performance of simulation to solve forming problem such as springback. The new developed tools are fabricated by using CNC machine with Solidwork and Mastercam software. The new developed tool is installed on the tensile test machine for bending and unbending experiment. The experimental load-extension data are converted to stress-strain data. The hardening parameters are identified using optimization software from Matlab. The fitting curve shows adjusted R-square values recorded are more than 0.9, which mean the parameters values identified are very good for fitting the experimental curves. Improvements in the newly developed tools are suggested to reduce the friction and specimen holding method by installing roller in the holder.